FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBANGUNAN INFRASTRUKTUR (JALAN DAN JEMBATAN ) DI KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR TAHUN 2011-2013 - Iles Sinta Lestari; M.Y.Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Road and bridge construction is a very important development. This is because roads and bridges are the interface between one region and another. Then, with the roads and bridges that deserves to be taken towards a region will also encourage the growth of the regional economy.However, this is not perceived by Kampar Kiri Hulu. Some areas in the region have not been touched for the construction of roads and bridges to their territory well. The absence of planning or development program created by the district government of Kampar be one of the factors that influence delays in the construction of roads and bridges in Kampar Kiri Hulu.Then, there is no political will from the government for the construction of roads and bridges.The intent of this study was to determine what factors influence the development of road infrastructure and bridges in Kampar Kiri Hulu. The method used in this study is a qualitative approach to the informant Head Kampar Kiri Hulu, Public Works Department, Government Administration Building Kampar, Kampar District Assembly Members and some people Kampar Kiri Hulu. With data collection techniques such as interviews and documentation. As well, the data analysis with qualitative assessment.Results from this study were 1) the factors that affect the process of infrastructure development of roads and bridges is the lack of willingness of local governments to do the construction or commonly called the political will and there is no planning of infrastructure development of roads and bridges are the focus for Kampar Kiri Hulu. 2) the absence of established communication top down bottom up (two-way communication) between the Government of the District of Kampar Kampar Kiri Hulu society, only from the bottom up. 3) lack of coordination among the implementing agencies goes well.